Pengaruh Konsep Diri dan Percaya Diri terhadap Kemampuan Kemampuan Berpikir Kritis Matematis - Aziz Nur Rohmat; Witri Lestari (Universitas Indraprasta PGRI, 2019)
Research was conducted at SMA Negeri 16 Jakarta with the aim of research to know the influence of self-concept and confident in the ability of critical thinking mathematically. The study method in the form of correlational surveys with double regression analysis. The research used is by classifying the concept of self and confident each student who will be attributed to the ability of critical thinking mathematically. After conducting research and analyzing data, the researchers finally can withdraw that: 1) There are significant positive influences of self-concept and self-confidence together against the student's mathematical critical thinking ability, 2) There is an insignificant positive influence on the self-concept of the student's mathematical critical thinking ability, and 3) there is an insignificant positive influence of confidence in the students mathematical critical thinking ability.